Implementation of Circular Economy and Its Effect on GRDP (Case Study of 15 Provinces in Indonesia) - Adinata, Hans; Emalia, Zulfa (Lafadz Jaya Publisher, 2024)
This research aims to analyze the variable influence of the amount of clean water distributed, waste generation, B3 waste from the manufacturing industry that is managed, and creative economy industry workforce on the GRDP of 15 Provinces in Indonesia. The analytical tool used is panel data regression. In the overall research period, the amount of clean water distributed had a positive and significant effect on GRDP. Meanwhile, waste generation has a positive and insignificant effect on GRDP. Meanwhile, processed B3 waste from the manufacturing industry has a negative and insignificant effect on GRDP. Meanwhile, creative economy industry workforce had a positive and insignificant effect on GRDP throughout the research period.